Teachers of Nasriyah School in the Kingdom of Granada - Al-Nasiri, Imad Tali Mahdi; Al-Faili, Zainab Jassim Muhammad (Journal of Ecohumanism, 2024)
The teacher is the Sheikh, the tutor, the polite, and the educator. Therefore, it must have moral features and high scientific capabilities. Based on this, great qualities distinguished the teachers in Islam, and it was an impressive path to trace by others. Therefore, the world preferred over the worshiper because of its importance and place in fighting everything that departs from the principles of Islam until it was said: 'One jurist is more severe on Satan than a thousand worshipers' (Yusuf, 1994, page 127). One of the most important concepts introduced by Islam is science. This word has its sanctity and carries everything that is for the good of all human beings. Knowledge: is the awareness of a thing in its true nature, and it is the light of God that He casts into the heart of the one he loves. Science: knowledge, and knowledge is applied to the totality of issues and universal principles that are united by one aspect, such as the science of theology and natural sciences. The Noble One, in places where he mentioned the importance of knowledge, God Almighty said: So know that, Lâ ilâha illallâh (none has the right to be worshipped but Allâh), and ask forgiveness for your sin, and also for (the sin of) believing men and believing women. And Allâh knows well your moving about, and your place of rest in your homes( )Surah Muhammad, verse 19 (. And the Almighty said: Is one who is devoutly obedient during periods of the night, prostrating and standing [in prayer], fearing the Hereafter and hoping for the mercy of his Lord, [like one who does not]? Say, "Are those who know equal to those who do not know?" Only they will remember [who are] people of understanding. ( )Surat Al -Zumar, Verse 9 . Sharia did not know a religion like Islam, which paid great attention to science, as it pushed minds into the field of science and knowledge and called them to open the horizons of thought, as it opened wide before them the book of the universe and called them to knowledge, contemplation, and observation of the universe to discover its secrets. God Almighty said:) But of no avail will be signs or warner to a people who do not believe( (Surat Yunus, verse: 101). Islam pushes a person to learn every knowledge that is beneficial to him, his society, and humanity as a whole, whether this knowledge is in the field of legal, social, or natural sciences, or other types of knowledge and sciences (Ahmed, 1991, p. 63). The first five verses revealed to the Prophet (peace be upon him) call him to knowledge. God Almighty said: Recite in the name of your Lord who created( (Surat Al-Alaq, verses 1) God raises the knowledgeable believer above the unknowing believer with the abundance of reward, and by Him, ranks are raised, and their elevation includes the moral in this world with a high status and good reputation, and the physical in the Hereafter with a high status in Paradise (Al-Asqalani, 1959 AD, p. 130). God Almighty said: "Arise," then arise; Allāh will raise those who have believed among you and those who were given knowledge, by degrees. And Allāh is Aware of what you do (. )Surah Al-Mujadila, verse 11.( And in the Almighty’s saying: ((And He found you lost and guided you. And He found you self-sufficient and enriched)) (Surat Ad-Duha, verses 7-8.) So God Almighty prioritized gratitude with knowledge over gratitude with money (Al-Hussein, 1999 AD, p. 200). There have been many Quranic verses that show the status of knowledge and scholars, including the Almighty saying: (God witnessed that there is no god but He and the angels( (Surat Al-Imran, verse 18). In this verse, God Almighty began himself and praised his angels and a third of the scholars, and they suffice them with honor, majesty, and noble (Al-Kinani, 1935 AD, page 5). The Almighty said: (The Most Merciful taught the Qur’an the man of the man taught him the statement) (Surat Al-Rahman, verses 1-4). Among the rational evidence for the virtue of knowledge is the Almighty’s saying: (Are those who know and those who do not know equal?) (Surat Az-Zumar, verse 9) He denied that the two groups are equal on the basis of preference for the people of knowledge. Just as the knowledgeable and the ignorant are not equal, the devout and the disobedient are not equal (Al-Shirazi, 1997 AD, p. 38). Science may be a deadly weapon and a destructive power that destroys civilization to the darkness of brutality and barbarism, and the initiatives of the world may be a productive force and a tool for the development and progress of life. And Islam determines the position of science and determines the responsibility of those in their hands the power of science and its means, and they must use it for construction, urbanism, and the development of man and its progress in the fields of life, not demolish and death and from the Qur’anic verses that indicate the status of scholars, the Almighty saying: (He only fears God from His servants, the scholars) (Surat Fatir, Verse 28). What is meant here is that no one fears God as He should be feared, nor is he wary of his sins out of fear of His wrath, except the scholars who truly know him, because the scholar is more wary of God’s punishment than the ignorant (Al-Hasan, D.T., page 407). The Almighty has commanded His servants to learn, saying, Almighty and Majestic: (So ask the people of The Remembrance if you do not know” (Surat An-Nahl, verse 4). Science is the light that we guide to the straight path, and the optimal life that every time requires with science lives the hearts as the earth lives with the rain of rain, and a people of people did not rise except with science, as it is the basis for every virtue, and by science a person guides to reveal the secrets of nature and employ them to serve it (Al -Qurtubi, 1986 AD, Page 28), Al -Tabrizi (Dad, 2012 AD, page 13) described the teachers, saying: 'The real teachers are transparent as crystal, the light of God crosses through them.'The teachers of the Nasserite School in the Kingdom of Granada will be supplied and their arrangement according to their deaths.